Menanam Pancasila Pada Generasi Z Di Tengah Gempuran Teknologi - Asep Nadhirin; Fauziah Zahra; Muhammad Fadhel Raihan; Rahma Dina Ariyanti; Rifiani Tasrifin; Haryo Wicaksono (Universitas Palan, 2024)
Nowadays, the development of globalization and technology has brought a lot of changes in the mindset, behavior and social identity of the community, especially for Generation Z. The resulting impact is also very significant on generation Z, so of course there must be a way to overcome these impacts. One very important thing is to instill the values of Pancasila in everyday life in this technological age. In this technological age, the values of Pancasila are very much needed for Generation Z in facing the times, especially to build the morals of Generation Z that remain moralized by Pancasila. We know for ourselves that Pancasila is the main foundation in the moral life in Indonesia and we can see now that many young people do not instill the values of Pancasila as the moral basis of their daily lives. In this article we want to tell readers how important it is to instill the values of Pancasila to Generation Z to create a generation that has morals in accordance with Pancasila.